FACTORS RELATED TO WORM INFECTION (SOIL TRANSMITTED HELMINTH) AND LEARNING ACHIEVEMENT AMONG ELEMENTARY STUDENTS AT WORK AREA OF PUSKESMAS PUNGGUR - Wulandari, Ayu; Saleh, Ismael; Silviana, Silviana (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2015)
Background : Helminthiasis is a public health problem in Indonesia. In some regions in Indonesia showed the prevalence of worm found in all age groups, but highest at the elementary school age children 90% to 100%. Clean and healthy lifestyle is factor the health problem. Worm infection can lead to cognitive impairment and there was correlation of learning achievement. Helminthiasis is still above the 2010 national number (<10%)……………………………, therefore this was considered important reducePurpose : This study aimed at discovering the risk factors related to worm infestation in elementary students and its impact on students’ achievement at work area of Puskesmas Punggur.Method : This research was conducted with cross sectional approach. As many as 88 samples were selected by using proportional random sampling. Result : The study revealed that there were 54,5% respondents who positively infected by worm infection. The corelated variables were bowel habit (p value=0,0007), foot ware (p value=0,041), hand washing habit (p=value 0,003), and nails hygiene (p value=0,000). There was correlation of worm infections and learning achievement (p value 0,0004). While the uncorrelated variables were snacking (p value 0,068) and playing on the ground (p value 0,0608).Advices : Based on the finding, Puskesmas Punggur should increase the health services (particularly for children) by conducting counseling on healthy lifestyle, carry on mass medication, and actively build a cross-sectoral cooperation in establishing school health centers. Also, the school should provide hygiene facilities and monitor the personal hygiene of the students. By doing these programs, the incidence of worm infection can be slowly reduced.Keywords : learning achievement, worm infection, PHBS respondents.